2008
DOI: 10.1057/palgrave.ces.8100248
|View full text |Cite
|
Sign up to set email alerts
|

Banking Competition and Efficiency: A Micro-Data Analysis on the Czech Banking Industry

Abstract: Abstract:Banking competition is expected to provide welfare gains by reducing monopoly rents and cost inefficiencies, favoring the reduction of loan rates and then investment. These expected gains are a major issue for transition countries in which bank credit represents the largest source of external finance for companies. With the use of exhaustive quarterly data for Czech banks, this paper aims at providing evidence on the effects of banking competition in the Czech Republic. First, we measure the level and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(40 citation statements)
references
References 45 publications
1
38
1
Order By: Relevance
“…The empirical evidence that supports this hypothesis is still scarce. For instance, Pruteanu-Podpiera and Weill (2008) have examined the effect of market power on efficiency in the Czech Republic, and found that greater market power is associated with greater efficiency. A similar story can be found in Maudos and DeGuevara (2007) for the case of the Spanish banking sector.…”
Section: Background and Related Literature Reviewmentioning
confidence: 99%
“…The empirical evidence that supports this hypothesis is still scarce. For instance, Pruteanu-Podpiera and Weill (2008) have examined the effect of market power on efficiency in the Czech Republic, and found that greater market power is associated with greater efficiency. A similar story can be found in Maudos and DeGuevara (2007) for the case of the Spanish banking sector.…”
Section: Background and Related Literature Reviewmentioning
confidence: 99%
“…However, few authors have used Granger causality test to estimate and investigate empirical relationship between bank performance and market competition. Pruteanu-Podpiera et al (2008), examined the Czech banking market between 1994 and 2005 and tried to estimate the effects of banking competition to efficiency. The results of their analysis rejected the quiet life hypothesis and indicated a negative relationship between competition and efficiency in banking.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For the Czech Republic they identifi ed the monopolistic competition using Panzar-Rosse model in 1995. Bikker and Spierdijk (2008 determined by Panzar-Rosse approach the monopolistic competition in the Czech Republic in 1999. Pruteanu-Podpiera et al (2008 showed in the Czech credit market growth in the absence of competition by Lerner index during the privatization period (1999)(2000)(2001)(2002).…”
Section: Concentration Of the Banking Sectormentioning
confidence: 99%